P. Heid. Inv. Kopt. 377: Zauberei in Text und Bild - Theis, Christoffer (Journal of Coptic studies, 2023)
Publication of the Coptic magical rag paper Inv. Copt. 377 from the papyrus collection in Heidelberg. This paper shows a picture made of letters and characteres for a magical ritual and two magical texts. The picture can possibly be interpreted as a special space, known as a"magical circle", for apotropaic purposes.